Aluminum profile and production process thereof

Through the introduction of hard anodization and diamond powder, combined with plasma-enhanced chemical vapor deposition, a protective layer is formed, which solves the problem of poor corrosion resistance of aluminum profiles and significantly improves its corrosion resistance in harsh environments.

CN119753783APending Publication Date: 2025-04-04CHIZHOU JIUHUA MINGKUN ALUMINUM IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411906144.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Aluminum profiles have poor corrosion resistance, especially in harsh environments that are prone to rapid corrosion.

Method used

The aluminum alloy substrate is treated with hard anodization, diamond powder is introduced, and diamond-like film is deposited by plasma-enhanced chemical vapor deposition to form a protective layer.

Benefits of technology

The corrosion resistance of aluminum profiles and the adhesion of coatings are improved, and the corrosion resistance is shown in particular in high salt spray environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses an aluminum profile and a production process thereof, belonging to the technical field of alloy materials. The production process comprises the following steps: an aluminum alloy substrate is first hard-anodized, and then diamond powder is deposited on the hard-anodized film layer or the film layer after pore expansion treatment, and finally a diamond-like film is deposited by plasma enhanced chemical vapor deposition method to closely combine with the introduced diamond powder to form a protective layer. After the aluminum alloy is hard-anodized, a pore expansion treatment can be performed, and after the pore expansion treatment, the micropore diameter and porosity of the hard-anodized film can be further increased to increase the adsorption amount and adsorption stability of the diamond powder. The preferred nucleation point in the subsequent deposition growth process is used to increase the diamond nucleation density and enhance the mechanical bite force between the coating and the substrate. The coating performance is optimized, thereby improving the corrosion resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to an aluminum profile and a production process thereof. Background Art

[0002] Pure aluminum has a low density and a low melting point. It is a face-centered cubic structure, so it has high plasticity, good corrosion resistance, and is easy to process. It can be made into various profiles and plates with good corrosion resistance. However, the strength of pure aluminum is very low and it is not suitable for structural materials. Aluminum profiles are aluminum alloy materials made by fusing pure aluminum with one or more other elements (such as copper, manganese, magnesium, silicon, zinc, etc.) to improve its strength, hardness, wear resistance, corrosion resistance and other properties. These added elements can improve the physical and chemical properties of pure aluminum, making aluminum alloys more suitable for various industrial applications.

[0003] Aluminum has high chemical activity and easily reacts with oxygen to form a dense oxide film (Al2O3), which can provide certain corrosion protection for aluminum alloys. However, in harsh environments, the oxide film is easily destroyed, causing rapid corrosion of aluminum alloys. Therefore, strict corrosion protection measures must be applied to aluminum alloys in practical applications. Anodic oxidation and organic coatings are usually used to protect aluminum alloys from corrosion. Good adhesion between the organic coating and the aluminum alloy surface is a prerequisite for long-term corrosion protection of aluminum alloys. However, most organic coatings are directly applied to the aluminum alloy surface, and their adhesion is poor.

[0004] Patent application with publication number CN1039626A discloses a method for chemical oxidation of aluminum and aluminum alloys. The method discloses a method for chemically oxidizing the surface of aluminum and its alloys using a chemical oxidation treatment solution composed of chromic anhydride, fluoride, potassium ferrocyanide, surfactant, rare elements, etc. After oxidation, the aluminum alloy oxide film is straw yellow. Since the oxide film formed by this method is chromate, chromium and its compounds will cause relatively serious environmental pollution and have poor environmental protection. Therefore, the above-mentioned chemical oxidation treatment method is limited due to the pollution problem. Summary of the invention

[0005] The purpose of the present invention is to provide an aluminum profile and a production process thereof to solve the problem of poor corrosion resistance of the aluminum profile.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A production process for aluminum profiles comprises the following steps: firstly, an aluminum alloy substrate is hard-anodized, then diamond powder is introduced into the hard-anodized film layer or the film layer after pore expansion treatment, and finally, a diamond-like film is deposited by plasma enhanced chemical vapor deposition method to closely combine with the introduced diamond powder to form a protective layer.

[0008] Furthermore, the hard anodizing of the aluminum alloy substrate refers to the aluminum alloy substrate being subjected to conventional alkaline degreasing and / or alkaline etching and nitric acid pickling and polishing treatment, followed by water washing and then hard anodizing treatment.

[0009] Furthermore, the hard anodizing solution in the hard anodizing process includes sulfuric acid, a corrosion inhibitor, aluminum ions and an acidic additive.

[0010] Furthermore, the content of sulfuric acid is 10% to 15%, the content of corrosion inhibitor is 0.1% to 0.5%, the content of aluminum ion is 0.1% to 0.5%, and the content of acidic additive is 1% to 5%.

[0011] Hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2 , final voltage 70-120V, air stirring, oxidation time 1-2h; the thickness range of hard anodized film is 30-60μm.

[0012] Furthermore, the aluminum alloy can be expanded after hard anodizing. The hard anodized film formed on the surface of the aluminum alloy after hard anodizing is porous. After the expansion, the micropore diameter and porosity of the hard anodized film can be further increased to increase the adsorption amount and adsorption stability of diamond powder. The expansion treatment adopts conventional acid expansion, and the expansion solution used in the acid expansion is sulfuric acid. The concentration of sulfuric acid in the expansion solution is 60-100g / L, the temperature is 20-30℃, and the time is 5-10min.

[0013] Furthermore, the introduction of diamond powder: the introduction of diamond powder into the micropores and surface of the hard anodized film and / or the micropores and surface of the hard anodized film after pore expansion treatment, the more uniform and stable the introduction of diamond powder is, the better the final coating performance is; the method of introducing diamond powder can be to first make the diamond powder into a dispersion, and then immerse or spray it.

[0014] Furthermore, the immersion process is as follows: an aluminum alloy substrate containing a hard anodized film and / or a hard anodized film that has undergone pore expansion treatment is added to a diamond powder ethanol dispersion (3-5 g / L) and immersed (ultrasonic dispersion can be performed to prevent excessive concentration in some areas), the immersion temperature is 25-30°C, and the time is 10-30 minutes.

[0015] The diamond powder (particle size ≤ 50 nm) in the dispersion is surface treated with a silane coupling agent.

[0016] Furthermore, the silane coupling agent may be γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, or the like.

[0017] Furthermore, the surface treatment step includes: adding diamond to alkali solution and stirring, then washing to neutral and drying. The diamond treated with alkali solution is reacted at 90-95°C in a toluene solution of silane coupling agent (the ratio of diamond, silane coupling agent and toluene is 5g: 0.05-0.1g: 1L) for 4 hours. After the reaction, it is washed with acetone for 3-4 times, vacuum filtered and dried.

[0018] After adsorbing diamond powder, a diamond-like film is deposited by plasma enhanced chemical vapor deposition to closely combine with the introduced diamond powder to form a whole, thereby improving the adhesion and corrosion resistance of the protective layer.

[0019] Furthermore, the process and process parameters of the plasma enhanced chemical vapor deposition described in the present invention are controlled as follows:

[0020] Before the plasma enhanced chemical vapor deposition is performed, the influence of oxygen and water vapor in the system must be eliminated. The air in the system is removed by introducing argon gas through vacuum pumping, and the water vapor in the system is removed by heating the system to 120° C.

[0021] The deposition temperature is 100°C, the deposition pressure is 2Pa; the voltage is 1400-1800V; the frequency is 600Hz; the reaction gases include argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20sscm, 10sscm and 0-20sscm respectively; the duration is 2h.

[0022] An aluminum profile is prepared by the production process.

[0023] Beneficial effects of the present invention:

[0024] The aluminum alloy substrate in the production process of the present invention is first hard-anodized, and then diamond powder is introduced into the hard anodized film layer or the film layer after pore expansion treatment, and finally a diamond-like film is deposited by plasma enhanced chemical vapor deposition to tightly combine with the introduced diamond powder to form a protective layer. Diamond powder is introduced through the multi-layer structure of the anodized film layer, and the preferential nucleation point in the subsequent deposition growth process is used to increase the diamond nucleation density and enhance the mechanical bite force between the coating and the substrate. The coating performance is optimized, and the corrosion resistance of the coating is thereby improved. The production process of the present invention can be applied to the surface treatment of a variety of aluminum alloy materials, the coating has high bonding strength, and the prepared aluminum profile has high corrosion resistance in a high salt spray environment, which has great advantages. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] 2024 aluminum alloy and 6061 aluminum alloy are both widely used materials. The same aluminum alloy material is selected in the embodiment and the comparative example, and 2024 aluminum alloy is used as the aluminum alloy substrate. The selected aluminum alloy substrate is subjected to conventional alkaline degreasing and / or alkaline etching and nitric acid pickling and polishing treatment, and then washed with water, and then the subsequent operation is carried out. The alkaline degreasing uses a sodium hydroxide aqueous solution with a mass fraction of 40% and is treated at 60° C. for 3 minutes. The pickling is a nitric acid solution with a mass fraction of 30% for pickling for 5 minutes. After the end, it is washed with water for 60 seconds and then used.

[0027] Example 1

[0028] This embodiment provides a production process of an aluminum profile, comprising the following steps:

[0029] Hard anodizing of aluminum alloy substrate: the content of sulfuric acid (98%) in the hard anodizing solution is 15%, the content of corrosion inhibitor (benzotriazole) is 0.5%, the content of aluminum ion is 0.5%, and the acidic additive (citric acid) is 5%. Hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2 , final voltage 120V, air stirring, oxidation time 1h; the thickness range of hard anodized film is 30-60μm.

[0030] The aluminum alloy substrate with hard anodized film was immersed in diamond powder ethanol dispersion (5 g / L) (ultrasonic dispersion was required to prevent excessive concentration in some cases), the immersion temperature was 25°C, and the time was 10 min. The diamond powder (particle size ≤ 50 nm) in the dispersion was surface treated with a silane coupling agent.

[0031] The surface treatment steps include: adding diamond to alkaline solution (0.15g / mL NaOH solution) and stirring at 90°C for 4 hours, then washing to neutral and drying. The diamond treated with alkaline solution is reacted at 90°C in a toluene solution of silane coupling agent (γ-aminopropyltriethoxysilane) (the ratio of diamond, silane coupling agent and toluene is 5g:0.1g:1L) for 4 hours. After the reaction, it is washed with acetone for 3 times, vacuum filtered and dried.

[0032] After the diamond powder is adsorbed, a diamond-like film is deposited on the aluminum alloy substrate pre-adsorbed with the diamond powder by plasma enhanced chemical vapor deposition.

[0033] The process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are as follows:

[0034] Before the plasma enhanced chemical vapor deposition is performed, the influence of oxygen and water vapor in the system must be eliminated. The air in the system is removed by introducing argon gas through vacuum pumping, and the water vapor in the system is removed by heating the system to 120° C.

[0035] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the frequency is 600Hz; the reaction gas includes argon and acetylene, wherein the flow rates of argon and acetylene are 20sscm and 10sscm respectively; the duration is 2h.

[0036] Example 2

[0037] This embodiment provides a production process of aluminum profiles, comprising the following steps:

[0038] Hard anodizing of aluminum alloy substrate: the content of sulfuric acid (98%) in the hard anodizing solution is 10%, the content of corrosion inhibitor (benzotriazole) is 0.1%, the content of aluminum ion is 0.1%, and the acidic additive (citric acid) is 1%. Hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2 , final voltage 70V, air stirring, oxidation time 2h; the thickness range of hard anodized film is 30-60μm.

[0039] The aluminum alloy substrate with hard anodized film was immersed in diamond powder ethanol dispersion (3 g / L) (ultrasonic dispersion was required to prevent excessive concentration in some cases), the immersion temperature was 30°C, and the time was 30 min. The diamond powder (particle size ≤ 50 nm) in the dispersion was surface treated with a silane coupling agent.

[0040] The surface treatment steps include: adding diamond to alkaline solution (0.10g / mL NaOH solution) and stirring at 90°C for 4h, then washing to neutral and drying. The diamond treated with alkaline solution is reacted at 90°C in a toluene solution of silane coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane) (the ratio of diamond, silane coupling agent and toluene is 5g:0.05g:1L) for 4h. After the reaction, it is washed with acetone for 3 times, vacuum filtered and dried.

[0041] After the diamond powder is adsorbed, a diamond-like film is deposited on the aluminum alloy substrate pre-adsorbed with the diamond powder by plasma enhanced chemical vapor deposition.

[0042] The process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are as follows:

[0043] Before the plasma enhanced chemical vapor deposition is performed, the influence of oxygen and water vapor in the system must be eliminated. The air in the system is removed by introducing argon gas through vacuum pumping, and the water vapor in the system is removed by heating the system to 120° C.

[0044] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the voltage pulse length is 10μs; the frequency is 600Hz; the reaction gas includes argon and acetylene, wherein the flow rates of argon and acetylene are 20sscm and 10sscm respectively; the duration is 2h.

[0045] Example 3

[0046] Compared with Example 1, the present embodiment is different in that the process and process parameters of plasma enhanced chemical vapor deposition are different. Specifically, the process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are controlled as follows:

[0047] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the voltage pulse length is 10μs; the frequency is 600Hz; the reaction gases include argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20sscm, 10sscm and 10sscm respectively; the duration is 2h.

[0048] Example 4

[0049] Compared with Example 1, the present embodiment is different in that the process and process parameters of plasma enhanced chemical vapor deposition are different. Specifically, the process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are controlled as follows:

[0050] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the voltage pulse length is 10μs; the frequency is 600Hz; the reaction gases include argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20sscm, 10sscm and 20sscm respectively; the duration is 2h.

[0051] Example 5

[0052] This embodiment provides a production process of aluminum profiles, comprising the following steps:

[0053] Hard anodizing of aluminum alloy substrate: the content of sulfuric acid (98%) in the hard anodizing solution is 15%, the content of corrosion inhibitor (benzotriazole) is 0.5%, the content of aluminum ion is 0.5%, and the acidic additive (citric acid) is 5%. Hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2, final voltage 120V, air stirring, oxidation time 1h; the thickness range of hard anodized film is 30-60μm.

[0054] After the hard anodizing treatment of the aluminum alloy, the hole expansion treatment is performed. The hole expansion solution used for the acid hole expansion is sulfuric acid. The concentration of sulfuric acid in the hole expansion solution is 60g / L, the temperature is 30°C, and the time is 10min. The aluminum alloy substrate with the hard anodized film after hole expansion is added to the diamond powder ethanol dispersion (3g / L) and soaked (in order to prevent the concentration of some parts from being too high, ultrasonic dispersion is required), the soaking temperature is 25°C, and the time is 10min. The diamond powder (particle size ≤50nm) in the dispersion is surface treated with a silane coupling agent.

[0055] The surface treatment steps include: adding diamond to alkaline solution (0.15g / mL NaOH solution) and stirring at 90°C for 4 hours, then washing to neutral and drying. The diamond treated with alkaline solution is reacted at 90°C in a toluene solution of silane coupling agent (γ-aminopropyltriethoxysilane) (the ratio of diamond, silane coupling agent and toluene is 5g:0.1g:1L) for 4 hours. After the reaction, it is washed with acetone for 3 times, vacuum filtered and dried.

[0056] After adsorbing the diamond powder, plasma enhanced chemical vapor deposition is used to allow the aluminum alloy substrate with the pre-adsorbed diamond powder and the subsequently deposited diamond-like film to be tightly combined to form a whole, thereby improving the adhesion and corrosion resistance of the protective layer.

[0057] The process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are as follows:

[0058] Before the plasma enhanced chemical vapor deposition is performed, the influence of oxygen and water vapor in the system must be eliminated. The air in the system is removed by introducing argon gas through vacuum pumping, and the water vapor in the system is removed by heating the system to 120° C.

[0059] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the frequency is 600Hz; the reaction gas includes argon and acetylene, wherein the flow rates of argon and acetylene are 20sscm and 10sscm respectively; the duration is 2h.

[0060] Example 6

[0061] This embodiment provides a production process of aluminum profiles, comprising the following steps:

[0062] Hard anodizing of aluminum alloy substrate: the content of sulfuric acid (98%) in the hard anodizing solution is 15%, the content of corrosion inhibitor (benzotriazole) is 0.5%, the content of aluminum ion is 0.5%, and the acidic additive (citric acid) is 5%. Hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2 , final voltage 120V, air stirring, oxidation time 1h; the thickness range of hard anodized film is 30-60μm.

[0063] After the hard anodizing treatment of the aluminum alloy, the hole expansion treatment is performed. The hole expansion solution used for the acid hole expansion is sulfuric acid. The concentration of sulfuric acid in the hole expansion solution is 100g / L, the temperature is 20°C, and the time is 5min. The aluminum alloy substrate with the hard anodized film after hole expansion is added to the diamond powder ethanol dispersion (3g / L) and soaked (in order to prevent the concentration of some parts from being too high, ultrasonic dispersion is required), the soaking temperature is 25°C, and the time is 10min. The diamond powder (particle size ≤50nm) in the dispersion is surface treated with a silane coupling agent.

[0064] The surface treatment steps include: adding diamond to alkaline solution (0.15g / mL NaOH solution) and stirring at 90°C for 4 hours, then washing to neutral and drying. The diamond treated with alkaline solution is reacted at 90°C in a toluene solution of silane coupling agent (γ-aminopropyltriethoxysilane) (the ratio of diamond, silane coupling agent and toluene is 5g:0.1g:1L) for 4 hours. After the reaction, it is washed with acetone for 3 times, vacuum filtered and dried.

[0065] After adsorbing the diamond powder, plasma enhanced chemical vapor deposition is used to allow the aluminum alloy substrate with the pre-adsorbed diamond powder and the subsequently deposited diamond-like film to be tightly combined to form a whole, thereby improving the adhesion and corrosion resistance of the protective layer.

[0066] The process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are as follows:

[0067] Before the plasma enhanced chemical vapor deposition is performed, the influence of oxygen and water vapor in the system must be eliminated. The air in the system is removed by introducing argon gas through vacuum pumping, and the water vapor in the system is removed by heating the system to 120° C.

[0068] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the frequency is 600Hz; the reaction gas includes argon and acetylene, wherein the flow rates of argon and acetylene are 20sscm and 10sscm respectively; the duration is 2h.

[0069] Example 7

[0070] Compared with Example 5, the difference between this embodiment is that the process and process parameters of plasma enhanced chemical vapor deposition are different. Specifically, the process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are controlled as follows:

[0071] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the voltage pulse length is 10μs; the frequency is 600Hz; the reaction gases include argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20sscm, 10sscm and 10sscm respectively; the duration is 2h.

[0072] Example 8

[0073] Compared with Example 5, the difference between this embodiment is that the process and process parameters of plasma enhanced chemical vapor deposition are different. Specifically, the process and process parameters of plasma enhanced chemical vapor deposition in this embodiment are controlled as follows:

[0074] The deposition temperature is 100°C and the deposition pressure is 2Pa; the voltage is 1400V; the voltage pulse length is 10μs; the frequency is 600Hz; the reaction gases include argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20sscm, 10sscm and 20sscm respectively; the duration is 2h.

[0075] Comparative Example 1

[0076] Compared with Example 1, the diamond powder in this comparative example is not subjected to surface treatment before use, and the other raw materials and preparation process remain the same as those in Example 1.

[0077] Comparative Example 2

[0078] Compared with Example 5, the diamond powder in this comparative example is not subjected to surface treatment before use, and the other raw materials and preparation process remain the same as those in Example 5.

[0079] Comparative Example 3

[0080] Compared with Example 5, in this comparative example, the aluminum alloy is hard anodized and then expanded. Sulfuric acid is used as the expansion solution for acid expansion. The concentration of sulfuric acid in the expansion solution is 200 g / L. The temperature is 30°C and the preparation time is 40 min. The remaining raw materials and preparation process remain the same as those in Example 5.

[0081] Comparative Example 4

[0082] Compared with Example 5, this comparative example does not perform hard anodizing treatment on the aluminum alloy, and the remaining raw materials and preparation process remain the same as those in Example 5.

[0083] Comparative Example 5

[0084] Compared with Example 5, this comparative example does not perform hard anodizing treatment on the aluminum alloy and does not introduce diamond powder. The remaining raw materials and preparation process remain the same as those in Example 5.

[0085] Performance tests were performed on Examples 1 to 8 and Comparative Examples 1 to 5: The coating adhesion was determined according to the VDI-3198 standard of the German Association of Science and Technology, with the adhesion grades ranging from HF1 to HF6 from good to poor; according to ASTM B117, after a 1000h, 5% neutral salt spray test, the coating was rated according to ASTM D1654 on a scale of 0-10, where 0 means that the coating has completely failed (such as large-scale peeling, severe corrosion of the base metal), and 10 means that the coating has almost no change and has excellent corrosion resistance.

[0086] The G200 nanoindenter was used to characterize the nanohardness of the protective layer on the surface of the aluminum profile. An area was randomly selected on the surface of the protective layer, and 20 points were pressed into the area in a rectangular array. The average nanohardness of the 20 points was taken as the hardness of the protective layer.

[0087] The results are shown in Table 1: Table 1

[0088] project Bonding strength level Neutral salt spray resistance test Hardness / GPa Example 1 HF2 8 11.31 Example 2 HF2 8 11.34 Example 3 HF1 8 11.59 Example 4 HF1 8 11.48 Example 5 HF1 8 11.71 Example 6 HF1 8 11.69 Example 7 HF1 9 11.82 Example 8 HF1 9 11.74 Comparative Example 1 HF5 5 10.02 Comparative Example 2 HF5 5 10.01 Comparative Example 3 HF4 5 10.55 Comparative Example 4 HF6 4 9.87 Comparative Example 5 HF6 4 9.86

[0089] It can be seen from Table 1 that the aluminum profile prepared according to the production process of the present invention has good corrosion resistance, the surface protective layer of the aluminum profile has high adhesion to the aluminum alloy substrate, high hardness, and good protective effect.

[0090] In Examples 1 to 8, the treated diamond powder is selected, which not only has a good dispersion effect, but also the addition of silane coupling agent can dope N and Si elements in the protective layer. The presence of Si-C bond will cause the original (without the introduction of N and Si elements) CC bond distortion and relaxation, which has a stabilizing effect on the sp3 structure. The bond length of the C=N bond is shorter than the CC bond, and then the degree of distortion of the carbon-based network structure in the protective layer is weakened, resulting in a decrease in the internal stress in the protective layer, and the bonding strength between the film and the substrate is improved. At the same time, as the degree of crosslinking increases, the hardness of the protective layer will also increase. In Examples 3 and 4, Examples 7 and 8, the source of N also includes reactive gas (nitrogen), but as the proportion of nitrogen in the reactive gas increases, the protective layer (phase structure of diamond-like film) will change, and a structure similar to the graphite phase will appear. The presence of the graphite phase will reduce the overall hardness of the film. Compared with Example 5, the untreated diamond powder (poor dispersibility and poor loading effect) selected in Comparative Examples 1 and 2 affects the subsequent deposition process, is not conducive to improving the bonding force of the protective layer, and thus affects the corrosion resistance of the aluminum profile. Compared with Example 5, the concentration of the pore expansion solution and the time control in Comparative Example 3 are different, which destroys the structure of the hard anodized film, affects the adhesion effect of the diamond powder, and also affects the subsequent deposition effect. In Comparative Examples 4 and 5, the aluminum alloy is not hard anodized, and it is difficult to introduce diamond powder, and the nucleation point cannot be preferentially formed, resulting in poor bonding between the subsequent protective layer and the aluminum alloy substrate, affecting the bonding strength of the protective layer.

[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for aluminum profiles, characterized in that: The method comprises the following steps: firstly, the aluminum alloy substrate is hard-anodized, then diamond powder is introduced into the hard-anodized film layer or the film layer after pore expansion treatment, and finally, a diamond-like film is deposited by plasma enhanced chemical vapor deposition method to closely combine with the introduced diamond powder to form a protective layer.

2. The production process of an aluminum profile according to claim 1, characterized in that: The hard anodizing of the aluminum alloy substrate refers to the aluminum alloy substrate being subjected to alkaline degreasing and / or alkaline etching and nitric acid pickling and polishing treatment, and then being washed with water and then hard anodizing.

3. The production process of an aluminum profile according to claim 1, characterized in that: The hard anodizing solution in hard anodizing includes sulfuric acid, corrosion inhibitor, aluminum ions and acidic additives.

4. The production process of an aluminum profile according to claim 3, characterized in that: The content of sulfuric acid is 10% to 15%, the content of corrosion inhibitor is 0.1% to 0.5%, the content of aluminum ion is 0.1% to 0.5%, and the content of acidic additive is 1% to 5%; And / or, hard anodizing uses direct current: the process conditions are temperature -7 ~ 5 ° C, current density 1 ~ 5A / dm 2 , final voltage 70-120V, air stirring, oxidation time 1-2h; the thickness range of hard anodized film is 30-60μm.

5. The production process of an aluminum profile according to claim 1, characterized in that: The pore expansion solution used in acid pore expansion is sulfuric acid, the concentration of sulfuric acid in the pore expansion solution is 60-100g / L, the temperature is 20-30℃, and the time is 5-10min.

6. The production process of an aluminum profile according to claim 1, characterized in that: Introduction of diamond powder: Diamond powder is introduced into the micropores and surface of the hard anodized film and / or the micropores and surface of the hard anodized film after pore expansion. The method of introducing diamond powder is to first make the diamond powder into a dispersion liquid, and then immerse or spray it.

7. The production process of an aluminum profile according to claim 6, characterized in that: The process of the immersion method is as follows: an aluminum alloy substrate containing a hard anodized film and / or a hard anodized film that has undergone pore expansion treatment is added to a diamond powder ethanol dispersion and immersed at a temperature of 25-30° C. for 10-30 minutes; the diamond powder in the dispersion is surface treated with a silane coupling agent; The particle size of the diamond powder is ≤50nm, and the content of the diamond powder in the diamond powder ethanol dispersion is 3-5g / L.

8. The production process of an aluminum profile according to claim 7, characterized in that: The silane coupling agent is one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane; The surface treatment steps include: adding diamond into alkaline solution and stirring, then washing to neutral and drying, taking the diamond treated with alkaline solution and reacting it in a toluene solution of silane coupling agent for 4 hours, and after the reaction is completed, washing with acetone, vacuum filtering and drying; the usage ratio of diamond, silane coupling agent and toluene is 5g:0.05-0.1g:1L.

9. The production process of an aluminum profile according to claim 1, characterized in that: The deposition temperature of the plasma enhanced chemical vapor deposition is 100° C., the deposition pressure is 2 Pa; the voltage is 1400-1800 V; the frequency is 600 Hz; the reaction gas includes argon, acetylene and nitrogen, wherein the flow rates of argon, acetylene and nitrogen are 20 sscm, 10 sscm and 0-20 sscm respectively; and the duration is 2 hours.

10. An aluminum profile, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Chemical oxidation process of aluminium and its alloy

    CN1039626A